Peningkatan Kreatifitas dan Kompetensi Wirausaha Berbasis Edukasi Ekspor pada UMKM Kota Depok - Nursyirwan, Vivi Iswanti; Ardaninggar, Sasmita Sari; Anggraini, Nova (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Community Service Program (PKM) focuses on Creativity and Entrepreneurial Competence in Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a crucial role in Indonesia's economy, but the number of business actors is still low, around 3%, compared to developed countries with 10%. Creativity and entrepreneurial competence are essential for MSMEs to remain competitive in the global market. One of the main challenges is the low competence of human resources, which impacts creativity and business sustainability. This program aims to enhance knowledge of export processes, regulations, and product development strategies to help MSMEs compete internationally. By improving their knowledge and skills, entrepreneurs can open up export opportunities and contribute to national economic growth. The program, held every semester, results in national journal articles with ISSN for activity publications. Research findings indicate that MSME actors in Cipayung, Depok, gained additional insights into exporting and marketing their products abroad. Participants expressed a desire for the program to continue and for future assistance in PKM activities.